Konsep Pendidikan Jasmani dalam Perspektif Al-Qur’an - Aulia, Mizar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Islam strongly emphasizes humans to always maintain their physical health. Physical health is important to make it easier for humans to carry out their activities both work and worship. Through a strong and healthy body, a brilliant Islamic civilization will be created. In the Qur'an itself, there are quite a number of verses that explicitly and implicitly explain the urgency of implementing physical education. This research aims to find out how the concept of physical education in the perspective of the Qur'an so that later it can be implemented into Islamic education for students and children. The results of this study indicate that physical education is very important to maintain health and a healthy lifestyle so as to avoid all kinds of diseases. The implication of physical education in Islamic education is that it leads to its implementation for students in the educational process contained in the curriculum, infrastructure facilities must also support the implementation of physical education in educational institutions. Parents and educators must collaborate in providing physical education to children or students.